Sarcasm Analysis Meme 'Adit, tolongin dit' Using Pragmatic Studies - Agustinah, Agustinah; Eryon, Eryon (Kajian Linguistik dan Sastra, 2026)
his study analyzes the forms and functions of sarcasm in viral memes and audio parodies on social media using a pragmatic approach. The results show that sarcasm does not merely function as a form of ridicule but becomes a mechanism of humor that emerges through the discrepancy between literal utterances and actual intentions. Based on Attardo's classification, the dominant forms of sarcasm in the data include aggressive sarcasm, mock politeness, ironic encouragement, and hyperbolic sarcasm, which function to criticize characters' behavior, express annoyance, and create comic effects through exaggerated emotional responses. All the data indicate that humor is formed through violations of Grice's maxims, particularly the maxims of quality, quantity, relevance, and manner. These violations do not signify a failure of communication but rather a deliberate linguistic strategy used to create digital humor. Additionally, memes work through a pragmatic construction based on emotional contrast—for example, when a request for help is met with a sarcastic response that enhances the comedic effect while making it easier for the audience to recognize the sarcasm. Overall, this study confirms that understanding sarcasm in digital culture depends on the pragmatic context and shared knowledge among users. Abstrak Studi ini menganalisis bentuk dan fungsi sarkasme dalam meme viral dan parodi audio di media sosial menggunakan pendekatan pragmatik. Hasil penelitian menunjukkan bahwa sarkasme tidak hanya berfungsi sebagai bentuk ejekan, tetapi menjadi mekanisme humor yang muncul melalui ketidaksesuaian antara ucapan literal dan niat sebenarnya. Berdasarkan klasifikasi Attardo, bentuk sarkasme yang dominan dalam data meliputi sarkasme agresif, sopan santun palsu, dorongan ironis, dan sarkasme hiperbolik, yang berfungsi untuk mengkritik perilaku karakter, mengekspresikan ketidaknyamanan, dan menciptakan efek komik melalui respons emosional yang berlebihan. Semua data menunjukkan bahwa humor terbentuk melalui pelanggaran terhadap maksim-maksim Grice, khususnya maksim kualitas, kuantitas, relevansi, dan cara. Pelanggaran ini tidak menandakan kegagalan komunikasi, melainkan strategi linguistik yang disengaja untuk menciptakan humor digital. Selain itu, meme bekerja melalui konstruksi pragmatik berdasarkan kontras emosional—misalnya, ketika permintaan bantuan dibalas dengan respons sarkastis yang memperkuat efek komedi sambil memudahkan audiens mengenali sarkasme. Secara keseluruhan, studi ini menegaskan bahwa pemahaman sarkasme dalam budaya digital bergantung pada konteks pragmatik dan pengetahuan bersama di antara pengguna.